PROJECT-BASED LEARNING - STEAM IN IMPROVING STUDENTS' ABILITY IN CHEMISTRY SUBJECT - kikis megowanto (PEDAGOGIA, 2022)
The PISA 2006-2018 report shows a less significant development of our country's literacy and scientific abilities. Hard work and more efficient methods are needed for the development of education in Indonesia, especially chemistry which is known as the central of science. The STEAM learning approach is believed to be able to improve the quality of learning, and make it interesting. The approach used in this research is the class observation of the Project Based Learning (PjBL) method, the STEAM (Science Technology Engineering Art Mathematic) approach, which is carried out by the students of SIS Kelapa Gading-Jakarta. There were two student groups who were observed completing assignments per semester over a period of 3 semesters (2 academic years). PjBL learning is better in terms of completeness than Non-PjBL. The difference in the percentage of task completeness is between 20-32%, the difference in value is between 10-24%. Furthermore, PjBL learning with STEAM is better than Non STEAM, with a difference in the percentage of task completeness 12%, the difference in value is 9%. This is because it makes students more engaged, happy, motivated, more understanding and in accordance with the learning needed in the 21st century.